2021
DOI: 10.1111/jocs.15765
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on coronary artery bypass graft surgery in Brazil: A nationwide perspective

Abstract: Introduction The coronavirus disease 2019 (COVID‐19) pandemic has been a worldwide challenge, and efforts to “flatten the curve,” including restrictions imposed by policymakers and medical societies, have forced a reduction in the number of procedures performed in the Brazilian Health Care System. The aim of this study is to evaluate the outcomes of coronary artery bypass graft (CABG) from 2008 to 2020 in the SUS and to assess the impacts of the COVID‐19 pandemic in the number of procedures and death rate of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…The results showed that in 2020, during the pandemic period, there was an average reduction of 25% in the number of CABG performed in Brazil, with the majority of procedures (75%) being performed in the south and southeast regions of the country. Regarding postoperative mortality, they observed an opposite effect with an increase in mortality from 5.6% to 6.3% during this pandemic period 6 …”
mentioning
confidence: 91%
See 3 more Smart Citations
“…The results showed that in 2020, during the pandemic period, there was an average reduction of 25% in the number of CABG performed in Brazil, with the majority of procedures (75%) being performed in the south and southeast regions of the country. Regarding postoperative mortality, they observed an opposite effect with an increase in mortality from 5.6% to 6.3% during this pandemic period 6 …”
mentioning
confidence: 91%
“…In this context, Kalil and Col 6 . examine the impact of the COVID‐19 pandemic in the number of procedures and death rate of coronary artery bypass graft (CABG) performed in 2020 in Brazil.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A significant number of surgical procedures have been cancelled or postponed due to allocation of resources during the pandemic. In the field of NCDs, remarkable declines in cardiovascular surgery have been reported in several countries [23][24][25][26][27]…”
Section: Disrupted Healthcare Servicesmentioning
confidence: 99%